Hedging belts, de-risking roads: Sinosure in China's overseas finance and the evolving international response - Yunnan Chen; Zongyuan Zoe Liu (Overseas Development Institute (ODI), 2023)
This report explores the development of Sinosure as an institution and its involvement in China's overseas lending and the Belt and Road Initiative (BRI).
Keywords: 330; Development finance; Multilateral institutions; China